Strategi Komunikasi dalam Merekrut Peserta Didik Baru di SMP Islam Al Abidin Surakarta - Idhan Khalik; Hamdan Daulay (AS-SABIQUN, 2022)
This research is motivated by the number of private educational institutions, especially those who are members of the Integrated Islamic School Network or JSIT and these institutions will carry out a communication strategy in introducing schools to the community and compete with each other to increase the number of students through the quality and quality of the school. In the midst of increasingly fierce competition, this will be taken into consideration in how to develop the most effective communication strategy to introduce the school to the wider community. This study aims to find out how the communication strategy used by Al Abidin Islamic Junior High School Surakarta in recruiting new students. The research approach used in this study is a qualitative descriptive research approach. The setting of the research was conducted at Al Abidin Islamic Junior High School. The subjects were the head of SMP Al Abidin and the deputy head of SMP Al Abidin in the field of curriculum. The informants of this research were the PPDB team, school principals and vice principals in the field of education. Methods of data collection using the method of documentation, interviews and observations. The results showed that the Communication Strategy carried out by Al Abidin Islamic Junior High School Surakarta was realized in three stages of strategy, namely strategy formulation, the second was strategy implementation and the final stage of strategy was strategy evaluation.